Futures of Modernity - Heinlein, Michael,Kropp, Cordula,Neumer, Judith (transcript Verlag, 2012)
Global risks, mobilities and interdependencies transnationalize local life and working worlds. These processes lead to an inner globalization of societies in which worldwide constellations of »reflexive« (Ulrich Beck), »multiple« (Shmuel N. Eisenstadt), »entangled« (Shalini Randeria) and »global« (Arjun Appadurai) modernities simultaneously and immediately clash in social action: a process of cosmopolitanization in which »the global« is localized and »the local« is globalized in radical new ways. In this book, an international selection of prominent critical thinkers address this premise and provide their interpretations of imminent challenges, concomitant social dynamics and political implications.With contributions by Arjun Appadurai, Zygmunt Bauman, Ulrich Beck, Elisabeth Beck-Gernsheim, Edgar Grande, Maarten Hajer, Ronald Hitzler, Wolf Lepenies, Anna Tsing, Angela McRobbie, Bruno Latour, Ted Nordhaus & Michael Shellenberger, Hans-Georg Soeffner, Natan Sznaider, Anja Weiß and Yunxiang Yan
Keywords: Aufsatzsammlung; Globalization; Politics; Risk; Society; Sociology; Political Theory; Political Philosophy; Sociological Theory; Cosmopolitanism; Anthropology; Globalisierung; Weltgesellschaft; Individualisierung; Risikogesellschaft; Soziale Ungleichheit; Weltbürgertum; Moderne